Rempah Lombok: Pendekatan Kearifan Lokal sebagai Strategi Penguatan Praktik MPASI bagi Kader Posyandu - Nani Nurhaeni; La Ode Abd Rahman; Astuti Astuti*; Syamikar Baridwan Syamsir; Ayuni Rizka Utami (Universitas Lancang Kuning, 2023)
Stunting is a problem of chronic malnutrition in young children. Some of the causes of stunting were inappropriate of complementary feeding practices and lack of support from health cadres. One of the stunting locus areas in Indonesia is East Lombok Regency. An education programme needs to be conducted for stunting prevention, such as education of complementary feeding practices and socialisation of the book called